Consumption Inequality and Intra-Household Allocations - Jeremy Lise; Shannon Seitz (Queen's University, Department of Economics, 2004)
The current literature on consumption inequality treats all adults within the household equally, making the implicit assumption that all consumption inequality is between, not within, households. However, increased marital sorting on earnings and the subsequent rise in the share of women's income in the household may have important implications for consumption inequality measured at the individual level. We use an extension of the collective framework of Chiappori to estimate a rule for assigning resources to individual household members. We then construct a measure of individual level inequality by looking at implied changes in intra-household allocations and explore the implications of our framework for the measurement of individual level, versus household level, consumption inequality. Our analysis, which is based on households comprising one or two adults, suggests that the conventional approach of ignoring intra-household allocations underestimates the level of cross-sectional consumption inequality by 30% and overstates the trend by two-thirds. Our findings also indicate that increases in marital sorting on wages and hours worked can simultaneously explain virtually all of the decline in within household inequality and a substantial fraction of the rise in between household inequality in the UK since the 1970s.
Keywords: D12; D13; D63; J12; J22; 330; Collective Model; Consumption Inequality; Marital Sorting; Privater Konsum; Privater Haushalt; Allokation; Gerechtigkeit; Großbritannien